'The streets have been watched regularly': the York Penitentiary Society, young working-class women, and the regulation of behaviour in the public spaces of York, c. 1845–1919. Issue 3 (16th April 2019) - Harrison, Laura
ABSTRACT: The York Penitentiary Society, a charitable female reformatory in York, aimed to transform 'fallen' women in the city into useful citizens through institutionalisation, domestic training, and moral and religious instruction. The Penitentiary focused on isolating its 'inmates' from wider society, but its moral reach extended far beyond the high walls of the Refuge, and the young women confined within. This article examines the York Penitentiary Society, and considers how it acted to police the streets and public spaces of York, and the behaviour of young women who populated them. In addition to adding detail to our understanding of the operation of female reform institutions, this study also adds to our knowledge on the unofficial policing of women's behaviour in public space, and has significant implications for histories of urban life.